Предмет: Математика, автор: sheshnevaira

СРОЧНОООО
5x*(3x-2)+2*(x-3)-3x*(4x+4)=3x²+14

Ответы

Автор ответа: svetazuna
2

5x*(3x-2) + 2*(x-3) - 3x*(4x+4) = 3x²+14,

15х²-10х + 2х-6 - 12х²-12х = 3x²+14,

3х²-20х-6 = 3x²+14,

-20х = 14 + 6,

-20х = 20,

х = -1

Автор ответа: NataMon
1

Ответ:

х = -1

Пошаговое объяснение:

5x* (3x-2) + 2* (x-3) - 3x* (4x+4 )= 3x²+14

15x² - 10х + 2х - 6 - 12x² - 12х = 3x²+14

15x² - 10х + 2х - 12x² - 12х - 3x² = 14 + 6

- 20х = 20

х = -20/20

х = -1

Похожие вопросы